Chromosome 1q21 aberrations identify ultra high‐risk myeloma with prognostic and clinical implications. Issue 9 (29th June 2022) - Kastritis, Efstathios; Migkou, Magdalini; Dalampira, Dimitra; Gavriatopoulou, Maria; Fotiou, Despina; Roussou, Maria; Kanellias, Nikolaos; Ntanasis‐Stathopoulos, Ioannis; Malandrakis, Panagiotis; Theodorakakou, Foteini; Sevastoudi, Aggeliki; Eleutherakis‐Papaiakovou, Evangelos; et al.
Abstract: Numerical abnormalities of chromosome 1q (+1q21) are common in patients with newly diagnosed multiple myeloma (MM) but their prognostic impact remains a matter of debate. In addition, the impact of the number of copies of 1q21 is not known. We analyzed 912 consecutive patients with symptomatic MM to evaluate the prognostic implications of +1q21 and of their copy number variations, as assessed by FISH. At the time of initial diagnosis, 249 (27.3%) patients had +1q21, of which 150 (16.4%) had 3 copies and 99 (10.9%) had 4 or more copies. Presence of +1q21 was associated with advanced ISS stage ( p = .003), concurrent presence of other cytogenetics aberrations and advanced R‐ISS stage ( p < .001). Patients with +1q21 had inferior PFS (median 34 vs. 20 months, p < .001) and OS (median 75 vs. 44 months, p < .001) but the copy number of 1q21 had no additional prognostic impact. In multivariate analysis, adjusting for R‐ISS, age, treatment and HDM, +1q21 remained an independent prognostic factor both for PFS ( p < .001) and OS ( p = .008). The detrimental prognostic effect of +1q21 was more profound in R‐ISS‐3 patients, identifying a subgroup with OS of just 16 months (vs. 46 for R‐ISS‐3 without +1q21, p < .001). We further validated our findings in an independent cohort of 272 patients. In conclusion, the presence of +1q21 is associated with more advanced disease, inferior PFS, and OS but especially patients with R‐ISS‐3 disease and +1q21 have a very poor outcome comprising an ultra‐high‐risk group. Abstract : Prognostic impact of +1q21 in the total population and in the validation cohort and prognostic impact among those with R‐ISS‐3 disease in the test and validation cohorts